2015
DOI: 10.22546/34/805
|View full text |Cite
|
Sign up to set email alerts
|

Nodular primary localized cutaneous amyloidosis: presentation of 2 case reports and literature review

Abstract: The nodular primary localized cutaneous amyloidosis is rare and characterized by skin deposition of amyloid substance. There are cases of progression to invasive disease. The type of amyloid substance is not specific to this disease, also being found in primary systemic amyloidosis or systemic amyloidosis associated with multiple myeloma. The authors describe two cases of nodular primary localized cutaneous amyloidosis. A 70-year-old man underwent excision of papule on the mouth left commissure, and a 39-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…PLCNA mainly occurs between the ages of 40 and 60, with the same proportion in men and women [ 11 ]. It is characterized by focal cutaneous predominant accumulation of light-chain immunoglobulins, secondary to a localized monoclonal proliferation of the plasma cells [ 12 ,13, 14 ]. In this case, amyloid originated from the immunoglobulin light chain and was associated with dermal plasma cell infiltration, which may penetrate the subcutaneous tissues and blood vessels and might develop into a systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…PLCNA mainly occurs between the ages of 40 and 60, with the same proportion in men and women [ 11 ]. It is characterized by focal cutaneous predominant accumulation of light-chain immunoglobulins, secondary to a localized monoclonal proliferation of the plasma cells [ 12 ,13, 14 ]. In this case, amyloid originated from the immunoglobulin light chain and was associated with dermal plasma cell infiltration, which may penetrate the subcutaneous tissues and blood vessels and might develop into a systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid protein in the nodular form is of AL type, which consists of monoclonal immunoglobulin light chain. [ 1 2 ] It is thought that AL amyloid in the cutaneous nodular form is produced by local plasma cells infiltrating the dermis. Some authors have reported a 7–50% risk of progression from localized nodular cutaneous amyloidosis to systemic forms on long-term follow-up.…”
mentioning
confidence: 99%